Analisis Mitigasi Bencana Di Pantai Greenbowl (Jurnal Destinasi Pariwisata, 2025)
Greenbowl Beach in Badung, Bali is a coastal tourist area with significant disaster risks, including tsunamis and cliff landslides. This research aims to analyze potential disasters and assess mitigation efforts using the 4A approach (Attraction, Accessibility, Amenities, Ancillary) and tourist perceptions. The method applied is descriptive quantitative through questionnaire distribution to 100 tourists. The findings show that most tourists are young adults (26–35 years old), predominantly male, coming from Jakarta and Melbourne. The primary activities are swimming and surfing. While 45% of respondents rated the evacuation route as very clear and 43% praised disaster response facilities, doubts remained about emergency preparedness and visitor capacity control. The study highlights the necessity of multilingual disaster information, improved awareness, and strengthened infrastructure to ensure tourist safety and sustainable destination management.